Homeowner Best Management Practices for the Home Lawn - Laurie E. Trenholm (EDIS, 2008)
Revised! ENH-979, a 5-page illustrated factsheet by Laurie E. Trenholm, provides easy-to-follow tips for maintaining a healthy lawn without polluting ground or surface water resources. It describes how to apply and store fertilizer, how to mow and irrigate your home lawn, and best practices for managing weeds effectively. Includes a table of recommended fertilizer rates for various home lawn grass species. Published by UF Department of Environmental Horticulture, December 2007.